Fertilizer source and application method influence sugarcane production and nutritional status - Castro, Sérgio Gustavo Quassi de; Coelho, Anderson Prates; Castro, Saulo Augusto Quassi de; Souza Chiachia, Thais Regina de; Castro, Rosilaine Araldi de; Lemos, Leandro Borges (Frontiers in Plant Science, 2023)
The contrasting weather conditions throughout the sugarcane harvest period in south-central Brazil (April to November) influence fertilization management in sugarcane ratoon. Through field studies carried out over two cropping seasons, we aimed to compare the performance of sugarcane at sites harvested in the early and late periods of the harvest season as a function of fertilizer sources associated with application methods. The design used in each site was a randomized block in a 2 x 3 factorial scheme; the first factor consisted of fertilizer sources (solid and liquid), and the second factor consisted of application methods (above the straw, under the straw, and incorporated into the middle of the sugarcane row). The fertilizer source and application method interacted at the site harvested in the early period of the sugarcane harvest season. Overall, the highest sugarcane stalk and sugar yields at this site were obtained with the incorporated application applying liquid fertilizer and under straw applying solid fertilizer, with increments of up to 33%. For the site harvested in the late period of the sugarcane harvest season, the liquid fertilizer promoted a 25% higher sugarcane stalk yield compared to the solid fertilizer in the crop season with low rainfall in the spring, while in the crop season with normal rainfall, there were no differences between treatments. This demonstrates the importance of defining fertilization management in sugarcane as a function of harvest time, thereby promoting greater sustainability in the production system.